PLACE BRANDING KAWASAN KOTA TUA AMPENAN, LOMBOK BERDASARKAN PERSEPSI DAN EKSPEKTASI STAKEHOLDERS - , REKTA DESKARINA, M. Sani Roychansyah, S.T., M.Eng., D.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Ampenan Old City is an asset former colonial history that is rich in tourism potential. It is the embryonic development of other cities in Lombok. The existence of some historic place basically will create value in tourism, which is supported by other live attractions. Ampenan Old City with a long faces should remain preserved as a symbol and character of the city. For that required place branding concept of Ampenan Old City. The application of place branding for a destination aims to change the perception of a place, including perceive the difference a place with other places to choose as a destination. This research aims to know the essential components of what role in place branding of Ampenan Old City according to perseptions and expectations of stakeholders. The combination between qualitative and quantitative method are used as the research method. The data collection are obtained by using questionnaires and interview. Meanwhile the the observation has also conducted in this research. Analysis of the data by using Importance-Performance Analysis with statistic descriptive. The result showed that an essential component which acts in place branding of Ampenan Old City according to stakeholders perseptions and expectations, is a component character. This component is considers very important but its performance now is not considers well. Component character needs to be improved its quality as the beginning of the concept of place branding of Ampenan Old City.